EFFECT OF RESIN PERCENTAGE AND CATALYST ON TENSILE AND IMPACT STRENGTH OF CARBON FIBER COMPOSITES - Nur Ahmad Syauqi, Fauzan; Wulansari, Ajeng; Indrianto Sudjoko, Rifdian (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The percentage of resins and catalysts can affect the mechanical properties of the composite, especially tensile and impact strength in carbon fibre-reinforced composites. The strength of composites tends to vary depending on several factors including the percentage of resin and catalyst, therefore to be able to create a quality composite the percentage calculation of resin and catalyst must be done. This study was conducted to find out in more detail the effect of resin and catalyst percentage on the tensile strength and impact of carbon fibre-reinforced composites. The method used in this study is an experimental method by testing 6 specimens of 2 and 3 layers which have catalyst percentages of 1%, 1.5%, and 2%. Based on the results of the study, it can be seen that the percentage of resin and catalyst significantly affects the tensile strength and impact, the greater the percentage of catalyst, the higher the tensile strength and the smaller the percentage of catalyst, the greater the impact strength of the composite. These results show that the percentage of resin and catalyst is one of the things that greatly affect the mechanical properties of carbon fibrereinforced composites.